2014
DOI: 10.1007/s00441-014-1990-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of distinct sub-cellular location of transglutaminase type II: changes in intracellular distribution in physiological and pathological states

Abstract: Transglutaminase type II (TG2) is a pleiotropic enzyme that exhibits various activities unrelated to its originally identified functions. Apart from post-translational modifications of proteins (peculiar to the transglutaminase family enzymes), TG2 is involved in diverse biological functions, including cell death, signaling, cytoskeleton rearrangements, displaying enzymatic activities, G-protein and non-enzymatic biological functions. It is involved in a variety of human diseases such as celiac disease, diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 63 publications
(65 reference statements)
3
40
0
1
Order By: Relevance
“…Indeed, recent compelling evidence places TG2 within the regulation of main pathways controlling the proteome homeostasis as autophagy, proteasome and exosomes . In keeping with this, there is a vast literature describing the deregulation of this enzyme during the pathogenesis of major human diseases (neurodegenerative, liver and respiratory disorders as well as cancer) in which there is a deregulated proteostasis that can be improved by modulators of TG2 activity . In spite of differences related to cell‐ and tissue‐specific disease context, these disorders share common features of unbalanced cell adaptation to either cell autonomous or environmental stress.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, recent compelling evidence places TG2 within the regulation of main pathways controlling the proteome homeostasis as autophagy, proteasome and exosomes . In keeping with this, there is a vast literature describing the deregulation of this enzyme during the pathogenesis of major human diseases (neurodegenerative, liver and respiratory disorders as well as cancer) in which there is a deregulated proteostasis that can be improved by modulators of TG2 activity . In spite of differences related to cell‐ and tissue‐specific disease context, these disorders share common features of unbalanced cell adaptation to either cell autonomous or environmental stress.…”
Section: Introductionmentioning
confidence: 98%
“…TG2 belongs to a class of enzymes known as the transglutaminases. TG2 is unique in this class of proteins, as it is ubiquitously expressed in all cell types within the brain, and can be found in most subcellular compartments (Espitia Pinzon et al, 2014; Grosso and Mouradian, 2012; Hilton et al, 1997; Hwang et al, 2009; Kim et al, 1999; Lesort et al, 1998; Lesort et al, 1999; Lorand and Graham, 2003; Mastroberardino et al, 2006; Piacentini et al, 2002; Piacentini et al, 2014; van Strien et al, 2011a; van Strien et al, 2011b). …”
Section: Introductionmentioning
confidence: 99%
“…TG2 subcellular localization in particular can significantly impact its ability to mediate intracellular signaling processes that contribute to cell death and survival [11,12,14,15]. In the present study we have shown that hypoxia, a central nervous system (CNS) injury-relevant stressor, increases neuronal expression of TG2, but has no effect on the expression of TG2 in astrocytes.…”
Section: Discussionmentioning
confidence: 55%
“…Intriguingly the ability of TG2 to protect neurons against ischemic stress is not dependent on transamidating activity [7,8], while the ability of TG2 to facilitate astrocyte migration [9] or potentiate ischemic-induced cell death [10] requires TG2’s transamidating activity. Further, its ability to mediate cell death and survival processes has been suggested to be dependent, in part, on its subcellular localization [1115]. In particular, targeting TG2 to the nucleus in various cell lines results in protection against a range of stressors [1114].…”
Section: Introductionmentioning
confidence: 99%